Diagnostic of generator partial discharge and acoustic imaging scheme for monitoring winding health condition and repair - Riyo Purnomo; Triyadi Nugraha Syaputra; Rian Suryadiningrat (Department of Electrical Engineering ITS and FORTEI, 2025)
Partial discharge in a generator is a phenomenon of electrical discharge that occurs in the generator winding insulation. This phenomenon, if it continues, will cause the generator winding insulation failure. Therefore, partial discharge needs to be monitored, both on-line and off-line. Currently, partial discharge monitoring equipment has been installed at the Cirata Hydroelectric Power Plant (PLTA Cirata), and routine off-line partial discharge testing has been carried out. With this data, it can be used as a reference for the necessary generator maintenance. If the partial discharge trending value increases 2 times in a year, maintenance is required. During maintenance, acoustic imager testing is carried out to map the location of the partial discharge. By combining the three types of testing, a good generator monitoring system will be obtained, and the right type of maintenance will be determined according to the partial discharge mapping results. The analysis begins by conducting on-line and off-line partial discharge trending. If the trending has exceeded the limit, mapping is then carried out with an acoustic imager during maintenance, and repairs are made according to the location and type of damage. Analysis of maintenance results is carried out by comparing the magnitude of the partial discharge value before and after maintenance. The maintenance results based on the test results of the three methods proved effective, this was indicated by a decrease in the off-line PD value from 751.3 nC to 3.792 nC and on-line PD from 23.92 nC to 1.059 nC.